Diagnosing Myasthenia Gravis With Repetitive Ocular Vestibular Evoked Myogenic Potentials - Wirth, Magdalena A.; Fierz, Fabienne C.; Valko, Yulia; Weber, Konrad P. (Frontiers in Neurology, 2020)
Timely and accurate diagnosis of myasthenia gravis, particularly in patients with fluctuating, isolated ocular involvement, remains challenging. Serological antibody testing and repetitive nerve stimulation of peripheral muscles usually have low sensitivity in these patients. Edrophonium testing may cause adverse events, single-fibre electromyography (SFEMG) is time-consuming and both tests are often unavailable outside specialized institutions. Repetitive ocular vestibular evoked myogenic potential (roVEMP) stimulation has recently been introduced to facilitate the diagnosis of myasthenia gravis. Similar to repetitive nerve stimulation, roVEMPs detect muscle decrements with the benefit of being non–invasive and allowing for direct measurement of the extraocular muscles. This review summarizes the clinical evidence of the diagnostic value of roVEMP for myasthenia. Prospective clinical trials have demonstrated high sensitivity and specificity. RoVEMPs are of particular interest in challenging myasthenia subgroups with isolated ocular involvement, negative serology, and/or negative conventional electrophysiological results. Optimal roVEMP repetition rates of 20-30 Hz have been identified. This promising novel diagnostic tool merits further attention and investigation to establish its value as a clinical test for myasthenia.